OLDES: new solution for long-term diabetes compensation management - Novák, Daniel; Štěpánková, Olga; Mráz, Miloš; Haluzík, Martin; Busuoli, Massimo; Uller, Miroslav; Malý, Karel; Nováková, Lenka; Novák, Petr (Conference proceedings ... Annual International Conference of the IEEE Engineering in Medicine and Biology Society, 2008)
EU project OLDES (Older People's e-services at home) aims at developing a very low cost and easy to use entertainment and health care platform designed to ease the life of older people in their homes. The platform is based on a PC corresponding to Negroponte's paradigm of a 100 $ device. OLDES combines user entertainment services (through easy-to-access thematic interactive channels and special interest forums supported by animators) and health care facilities. The pilot case study of diabetes type II compensation under the OLDES framework is presented. Apart from measurement of continuous glucose, blood pressure and weight, the user feeds into OLDES system food daily consumption using interactive food scales via user friendly software interface designed by user-centered design paradigm and obtains advice if necessary.
Keywords: financování organizované; Telephone; Signal Processing, Computer-Assisted; péče o sebe; Feasibility Studies; monitorování fyziologických funkcí; počítačové zpracování signálu; Health Services Accessibility; Monitoring, Physiologic; dostupnost zdravotnických služeb; Diabetes Mellitus, Type 2; software; lidé; Blood Glucose; telefon; Hypoglycemic Agents; Pilot Projects; diabetes mellitus 2. typu; pilotní projekty; Insulin; Algorithms; Financing, Organized; hypoglykemika; studie proveditelnosti; Internet; Self Care; algoritmy; Software; inzulin; krevní glukóza; internet; Humans